Empowering Islamic Boarding School Students through Santripreneur Education to Increase Learning Motivation and Economic Independence at Cendikia Mandiri Lebak Islamic Boarding School - Wijaya Kusuma, Jaka; Hamidah; Rini, Puput Puspito; Ahmad, Daelami (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Islamic boarding schools play a strategic role in fostering students’ character and preparing them for economic independence. However, limited exposure to entrepreneurship remains a challenge for many students in responding to contemporary socio-economic demands. This community service activity aims to empower students through a santripreneur education program to enhance learning motivation and promote economic independence at Cendikia Mandiri Islamic Boarding School, Lebak. This program employed a participatory approach involving preparation, implementation, evaluation, and follow-up stages. The activities included entrepreneurship training, motivational sessions, interactive discussions, and mentoring in a developing context-based business idea. Data were collected through observation, student participation records, and reflective evaluation. The results indicate an improvement in students’ learning motivation, as reflected in increased engagement in learning activities and stronger interest in entrepreneurship-related subjects. In addition, several students initiated small-scale business activities, such as food production, services, and cooperative-based enterprises. The program also contributed to enhancing students’ self-confidence, independence, and entrepreneurial awareness. In conclusion, the santripreneur education program serves as an effective approach to integrating character education with entrepreneurial skill development, while supporting the formation of students’ economic independence within the Islamic boarding school context.